Evaluation of lubrication potential of Ni3Al-WS2-Cu-doped hBN self-lubricating hybrid composites - Mahto N.K.; Tyagi R.; Sinha S.K.; Kaur M. (My University, 2025)
The lubricating potential of WS2 and Cu-doped hBN nanosheets (Cu-hBN) as solid lubricants in Ni3Al-based composites has been evaluated by conducting wear tests from room temperature (RT) to 800 °C. The results indicate a decreasing trend of coefficient of friction with increasing temperature from RT to 800 °C with Ni3Al showing the highest wear rate as well as coefficient of friction (0.65–0.42) and Ni3Al-WS2-Cu-hBN (0.44–0.18) showing the lowest at all the temperatures except at RT, 200 and 400 °C, at which Ni3Al-WS2 has the lowest coefficient of friction. The improved performance of Ni3Al-WS2-Cu-hBN reflects a cooperative synergy between WS2 and Cu-hBN at temperatures beyond 400 °C, whereas the combination did not reveal any assistive action below 400 °C. © 2023 Elsevier Ltd